2014
DOI: 10.1186/1756-0500-7-828
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use disorders and associated factors among people living with HIV who are attending services in south west Ethiopia

Abstract: BackgroundAlcohol use disorders (AUDs) in persons living with human immunodeficiency virus (PLHIV) in high-income countries have been associated with poor adherence to antiretroviral medications and worse HIV-related outcomes. Little is known about AUDs among people attending HIV services in sub-Saharan Africa.MethodsAcross-sectional study was carried out among PLHIV who attended HIV services at Jimma University Specialized Hospital in September 2012. The World Health Organization’s Alcohol Use Disorders Ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
107
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(133 citation statements)
references
References 24 publications
19
107
7
Order By: Relevance
“…This may be due to the difference between tools used in this study (AUDIT vs. CAGE), as the CAGE is designed to detect more severe AUDs and the difference in the study community. However, the prevalence of AUDs found in this study was almost similar to estimates from the study conducted in a psychiatric hospital in Switzerland, using AUDIT score cut off of 8, showed that the frequency of alcohol use disorder was 35.1% [33] and a cross sectional study done on alcohol use disorders and associated factors among people living with HIV who are attending services in southwest Ethiopia the prevalence of alcohol use disorders was 32.6% [43].…”
Section: Discussion Prevalence Of Alcohol Use Disorderssupporting
confidence: 85%
“…This may be due to the difference between tools used in this study (AUDIT vs. CAGE), as the CAGE is designed to detect more severe AUDs and the difference in the study community. However, the prevalence of AUDs found in this study was almost similar to estimates from the study conducted in a psychiatric hospital in Switzerland, using AUDIT score cut off of 8, showed that the frequency of alcohol use disorder was 35.1% [33] and a cross sectional study done on alcohol use disorders and associated factors among people living with HIV who are attending services in southwest Ethiopia the prevalence of alcohol use disorders was 32.6% [43].…”
Section: Discussion Prevalence Of Alcohol Use Disorderssupporting
confidence: 85%
“…(18) Patients with a CD4 + T lymphocyte count below 200 cells/ mm 3 had higher chances of being a lower alcohol user, while individuals with an undetectable viral load are more likely to use alcohol. (1) Regarding adherence to pharmacological treatment, it was observed that most patients had adequate adherence to ART, diverging from the previous research. (19)(20)(21) This result may be related to the fact that only 12 individuals in this study were classified as in harmful use of alcohol, probably due to the small number of people.…”
Section: Discussionmentioning
confidence: 59%
“…Advances in the health area, and the implementation of preventive measures and control of HIV infection have reduced the detection of new cases of AIDS; in contrast, people living with HIV/ AIDS (PLWHA) have increased their use of substances that lead to dependence (1) and this influences this population's social, economic, and psychological life. (2) The use of alcohol by PLWHA is related to a worse prognosis, with increased morbidity and mortality, (3) high-risk sexual behaviors, accelerated disease progression, low adherence to antiretroviral therapy (ART), CD4+ T lymphocyte decline, and increased viral load, as well as the spread of HIV infection, because alcoholics are more likely to have unprotected sex, favoring virus transmission.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In addition to adverse health effects, alcohol use in this population could facilitate secondary HIV transmission if it increases engagement in unprotected sex. Research in African populations has reported associations between alcohol use and having more sex partners, unprotected sex, and sexually transmitted infections (STIs).…”
Section: Introductionmentioning
confidence: 99%